THE STATUS AND RIGHTS OF THE CHILD IN THE SAME-SEX UNION: EUROPEAN LAW AND PRACTICE: EUROPEAN LAW AND PRACTICE - Vujović, Ranka (Pravni zapisi, 2022)
Parental rights are obviously the most controversial issue in the legal regulation of same-sex unions. This is one of the challenges facing the Republic of Serbia at this moment and which needs to be comprehensively considered in order to meet the announced legal regulation of same-sex unions, and this work is directed towards that goal. The focus of the paper is not the discussion about how the sexual orientation of parents affects the quality of parenting and the well-being of children and whether the sexual identity of parents is an important factor in effective parenting. This work is the result of research on how in the European legal area, in the member states of the Council of Europe and the European Union, which have legally regulated same-sex unions, the principles of equality, the rule of law, and the best interests of the child are reflected on the legal position of children and the enjoyment of rights arising from family life. In addition to the various points of view presented in the legal literature, the paper presents key positions and the latest decisions of the European Court of Human Rights and the European Court of Justice, which have specific implications for the need to harmonize internal regulations and legal practice in the member states, and a critical review of jurisprudence is given of certain foreign courts of the highest rank in cases whose outcomes can significantly influence the change of doctrines in the judicial practice of those countries, but also as an inspiration to other legal systems.
Keywords: child; parents; same-sex partner; marriage; same-sex unions; family life; personal relationships; alimentation; adoption; foster care